2021
DOI: 10.1088/2631-8695/ac372d
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on cladding with metal cored wire using GMAW process and parametric optimization

Abstract: Cladding is widely used in manufacturing industries for the production of pressure vessel by depositing thick layer of filler material for providing corrosion resistant-surface. The use of metal cored wire in gas metal arc welding (GMAW) process is popular due to its higher deposition rate and productivity. This work investigates the effect of process parameters on the deposition of cladding layer with ER 309L metal core wire (as filler material) on a corrosion resistant material (IS 2062). The welding paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Karadeniz et al observed that as welding speed increases, penetration increases to a maximum point where higher speeds result in a decrease in penetration [104]. Two parameter optimization studies for GMAW using RSM confirm this behavior [105,106].…”
Section: Shape and Dilution Of The Depositsmentioning
confidence: 89%
“…Karadeniz et al observed that as welding speed increases, penetration increases to a maximum point where higher speeds result in a decrease in penetration [104]. Two parameter optimization studies for GMAW using RSM confirm this behavior [105,106].…”
Section: Shape and Dilution Of The Depositsmentioning
confidence: 89%
“…Additional evidence of the effectiveness of HTS in optimising the goal function was provided by 3D surface plots for DOP. Ashish et al [16] deposited a cladding layer with ER309L filler material using a GMAW process on mild steel (2062 grade) plate. It was concluded that the RSM-JAYA optimisation procedure had given an optimal result.Bishub et al [17] utilised L27 Box-Behnken experimental design, to investigate multiple optimisation of weld bead characteristics during the GTAW welding of INCONEL 825 plate of 2.5 mm thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on GMAW welding showed that variations in current and voltage with 1mm diameter filler affected the mechanical properties of hardness and tensile strength of commercial steel and it was found that changes in physical properties resulted in changes in the strength of the welded product [1] [4]. It was also found that welding speed as a process parameter influenced the optimization of welding results [9] by deposition of a cladding layer with ER 309L metal core wire in GMAW welding [6]. In addition, GMAW welding speed parameters using the Taguchi method are used to optimize the tensile strength of the welding results [11].…”
Section: Introductionmentioning
confidence: 99%